2009
DOI: 10.1097/bpo.0b013e3181a6bfe8
|View full text |Cite
|
Sign up to set email alerts
|

Physeal Fractures of the Distal Tibia

Abstract: Level III: Retrospective Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(76 citation statements)
references
References 18 publications
7
60
0
7
Order By: Relevance
“…The single patient who did have a low AOFAS score (83) had had a motor vehicle accident and presented with an open injury. High-energy trauma is a risk factor for poor clinical outcomes (Leary et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single patient who did have a low AOFAS score (83) had had a motor vehicle accident and presented with an open injury. High-energy trauma is a risk factor for poor clinical outcomes (Leary et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Premature physeal closure causes growth disturbance (Barmada et al 2003). Leary has demonstrated that high-energy trauma is more likely to cause growth arrest than low-energy trauma or sports-related injuries (Leary et al 2009). In our study, 2 patients with premature physeal closure were in motor vehicle accidents, and 1 suffered a sports-related trauma.…”
Section: Discussionmentioning
confidence: 99%
“…8, 38 The prognosis of SH-I and SH-II is the best, followed by SH-III then SH-IV. This is believed to correlate with the magnitude of initial traumatic force and the resultant physeal injury.…”
Section: Fracture Classificationmentioning
confidence: 99%
“…Repeated or delayed manipulation of physeal fractures should be avoided, so as to avoid additional damage to the physis with incurrent risks of premature closure. 38, 41 …”
Section: Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation